2021
DOI: 10.1021/acs.jmedchem.0c01835
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Selective Methylenephosphonic Acid CD73 Inhibitors

Abstract: Solid tumors are often associated with high levels of extracellular ATP. Ectonucleotidases catalyze the sequential hydrolysis of ATP to adenosine, which potently suppresses T-cell and NK-cell functions via the adenosine receptors (A2a and A2b). The ectonucleotidase CD73 catalyzes the conversion of AMP to adenosine. Thus, increased CD73 enzymatic activity in the tumor microenvironment is a potential mechanism for tumor immune evasion and has been associated with poor prognosis in the clinic. CD73 inhibition is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Previous X-ray structural data clearly showed that the C6-NH 2 group of 5 was oriented toward a solvent-exposed area, which provided ample opportunity for derivatization. [56][57][58]60,61 Indeed, improved potency was observed upon substitution of the C6 position of the nucleobase with an array of alkyl-and benzylamines, consistent with previous observations by Muller and co-workers 45,72−74 (selected examples are shown in Table 3). Compounds derived from β-fluoroarabinose generally exhibited favorable PK profiles, with long half-lives and low plasma clearance in rats (e.g., 29, CL = 0.021 L h −1 kg −1 ).…”
supporting
confidence: 86%
See 3 more Smart Citations
“…Previous X-ray structural data clearly showed that the C6-NH 2 group of 5 was oriented toward a solvent-exposed area, which provided ample opportunity for derivatization. [56][57][58]60,61 Indeed, improved potency was observed upon substitution of the C6 position of the nucleobase with an array of alkyl-and benzylamines, consistent with previous observations by Muller and co-workers 45,72−74 (selected examples are shown in Table 3). Compounds derived from β-fluoroarabinose generally exhibited favorable PK profiles, with long half-lives and low plasma clearance in rats (e.g., 29, CL = 0.021 L h −1 kg −1 ).…”
supporting
confidence: 86%
“…Selected examples are highlighted in Figure 3, including AB680 (6), 56−59 a remarkably potent and selective inhibitor developed by Arcus Biosciences that was the first small-molecule CD73 inhibitor to enter clinical trials. A variety of nucleoside-derived compounds have been reported by researchers across academia and industry, including by Muller and co-workers (e.g., 7− 10), 45,[72][73][74][75][76]80 Peloton Therapeutics (11), 66 Arcus Biosciences (12), 60,61 ORIC Pharmaceuticals (13), 64,65 Calithera Biosciences ( 14), 52 and Vitae Pharmaceuticals/Boehringer Ingelheim (15), 54 among others. 67 Guided by the X-ray cocrystal structure of 5 and CD73, Muller and co-workers designed and synthesized a wide variety of AMPCP analogs with improved potency and metabolic stability, including C2-chloro analog 7 (Figure 3) 72,76 and PSB-12379 (8), which bears a benzylamine substituent at C6 of the nucleobase and displayed a K i of 2.21 ± 0.40 nM vs hCD73.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“… 25 The crystal structure of CD73 in complex with AMPCP (accession code: 4H2I) and small-molecule antagonist (accession code: 6YE2) were downloaded from PDB. 26 , 27 The co-crystal ligand (accession code: 6YE2) was modified to SHR170008. By selecting SHR170008 and the surrounding residues within 4.5Å, iterative energy minimizations with gradually increased tether deviations were performed to relax the clash between the ligand and protein while forming multiple interactions between ligand and protein.…”
Section: Methodsmentioning
confidence: 99%